Exploring family travel motivation, preference, and decision-making with children of different ages - Tzuhui Angie Tseng; Hsiu-Wen Chien; Ching-Cheng Shen (Tourism & Management Studies)
Family tourism has seldom been explored beyond the consideration that families that travel with children are a homogeneous group. This lack of studies is particularly true concerning the exploration of the differences among families with children of different ages. Therefore, this study aims to explore whether differences exist among travel motivations, travel preferences, key travel considerations, and travel characteristics of families with children of different ages. This study also sought to uncover whether differences exist in modes of decision-making concerning family tourism, travel frequency, travel length, dining outlets, accommodation, and modes of transportation among families with children of different ages. A questionnaire based on the literature was applied to Taiwanese families, and 608 valid responses were obtained. The results revealed that the different ages of the children determine travel motivation, decision-making, tourism activities, travel length, safety and hygiene, dining options, and accommodation. These results, which are novel in tourism literature, are discussed, and practical implications are drawn.